GREEN HUMAN RESOURCE MANAGEMENT: INTEGRATING SUSTAINABILITY INTO PERFORMANCE MANAGEMENT AND EMPLOYEE VALUE PROPOSITIONS - Rika Yusman; Dhenny Asmarazisa; Catur Fatchu Ukhriyawati (RADJA PUBLIKA, 2026)
Green Human Resource Management (GHRM) has emerged as an important organizational strategy for integrating sustainability into human resource practices and organizational management systems. This study employs a narrative literature review approach to examine the role of GHRM in integrating sustainability into performance management and employee value propositions. The findings indicate that green HR practices such as green recruitment, environmental training, sustainable reward systems, and green performance management contribute positively to organizational sustainability, employee engagement, and operational efficiency. The study also reveals that sustainability-oriented Employee Value Proposition (EVP) enhances employee attraction, satisfaction, and organizational loyalty, particularly among employees who value environmentally responsible workplaces. Furthermore, integrating environmental objectives into performance management systems encourages accountability and environmentally responsible employee behavior. However, challenges related to organizational resistance, performance measurement, and sustainability implementation remain significant. This study contributes to the literature on sustainable HRM by providing insights into the relationship between GHRM, sustainability performance, and employee outcomes in modern organizations.